Mental Health Literacy among Generation Z: A Systematic Literature Review - Zain, Nabilah (Psychology and Flourishing Humanity; Vol 2 No 1 (2025): Proceedings Conference on Psychology and Flourishing Humanity, 2026)
The increasing prevalence of mental health problems among adolescents and young adults has highlighted Mental Health Literacy (MHL) as a key determinant of early recognition, stigma reduction, and help-seeking. Generation Z (Gen Z), born between 1997 and 2012, is especially vulnerable due to constant digital exposure, academic demands, and socio-cultural transitions. This study systematically reviews empirical evidence on MHL among Gen Z, with particular attention to the Indonesian context. A Systematic Literature Review (SLR) was conducted following PRISMA 2020 guidelines, covering studies published between 2015 and 2025. Searches across Scopus, PubMed, Web of Science, PsycINFO, and Google Scholar yielded 312 records; 15 met eligibility criteria. The findings indicate that Gen Z generally demonstrates low-to-moderate levels of MHL, with misconceptions and stigma particularly pronounced in ASEAN countries, including Indonesia. The Mental Health Literacy Scale (MHLS) was the most frequently employed instrument, though cultural adaptation remains necessary. Gender, educational exposure, and digital engagement emerged as key predictors. Curriculum-based and digital interventions improved MHL in the short term, but evidence of long-term sustainability was limited. This review contributes novelty by mapping MHL among Indonesian Gen Z within global and regional contexts, highlighting gaps such as the absence of longitudinal studies, underexplored positive dimensions of MHL, and the influence of digital misinformation. The findings underscore the need for educational policy integration, culturally sensitive interventions, and evidence-based public health strategies to enhance resilience and promote accurate mental health understanding among youth.